ChemInform Abstract: Hydroxo‐Bridged Copper(II) Cubane Complexes. Issue 50 (November 2016) - Ardizzoia, G. Attilio; Brenna, Stefano
Abstract: Review: structural characterization, syntheses and magnetic behavior; 111 refs.